Dissociation of charge-transfer states at donor–acceptor interfaces of organic heterojunctions - Inche Ibrahim, Mohd Lukman (Institute of Physics, 2017)
The dissociation of charge-transfer (CT) states into free charge carriers at donor–acceptor (DA) interfaces is an important step in the operation of organic solar cells and related devices. In this paper, we show that the effect of DA morphology and architecture means that the directions of CT states (where a CT state’s direction is defined as the direction from the electron to the hole of the CT state) may deviate from the direction of the applied electric field. The deviation means that the electric field is not fully utilized to assist, and could even hinder the dissociation process. Furthermore, we show that the correct charge carrier mobilities that should be used to describe CT state dissociation are the actual mobilities at DA interfaces. The actual mobilities are defined in this paper, and in general are not the same as the mobilities that are used to calculate electric currents which are the mobilities along the direction of the electric field. Then, to correctly describe CT state dissociation, we modify the widely used Onsager–Braun (OB) model by including the effect of DA morphology and architecture, and by employing the correct mobilities. We verify that when the modified OB model is used to describe CT state dissociation, the fundamental issues that concern the original OB model are resolved. This study demonstrates that DA morphology and architecture play an important role by strongly influencing the CT state dissociation as well as the mobilities along the direction of the electric field.